2009
DOI: 10.1177/1028315309348737
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Exploring the Role of Studies Abroad in Nurturing Global Citizenship

Abstract: A conceptual framework, adapted from the Value-Belief-Norm theory, is proposed for understanding the role of studying abroad in nurturing global citizenship. The framework is oriented in concepts of justice, the environment, and civic obligations as key issues in the predictive validity of values, beliefs, and norms. The VBN approach is then applied to the design and experience of a short-term, faculty-led, educational travel study abroad program. By demonstrating how such theoretical contributions can help mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 59 publications
2
120
0
4
Order By: Relevance
“…Como señalamos antes, en el contexto de un mundo globalizado es posible comprender la ciudadanía en un continuo entre una ciudadanía consciente y una más crítica que va desde un i) actuar responsable en su comunidad; (ii) una actitud participativa en agrupaciones cívicas y/o comunitarias y iii) la conformación de un sentido crítico; hasta iv) el enfrentamiento de las injusticias identificadas (Tarrant, 2011). Entre los entrevistados/as encontramos ejemplos de las 4 formas mencionadas, agrupables más bien en dos grandes categorías a) un actuar responsable y participativo; y b) la evaluación permanente de los problemas de su entorno social.…”
Section: Entre Una Ciudadanía Consciente Y Una Ciudadanía Críticaunclassified
See 2 more Smart Citations
“…Como señalamos antes, en el contexto de un mundo globalizado es posible comprender la ciudadanía en un continuo entre una ciudadanía consciente y una más crítica que va desde un i) actuar responsable en su comunidad; (ii) una actitud participativa en agrupaciones cívicas y/o comunitarias y iii) la conformación de un sentido crítico; hasta iv) el enfrentamiento de las injusticias identificadas (Tarrant, 2011). Entre los entrevistados/as encontramos ejemplos de las 4 formas mencionadas, agrupables más bien en dos grandes categorías a) un actuar responsable y participativo; y b) la evaluación permanente de los problemas de su entorno social.…”
Section: Entre Una Ciudadanía Consciente Y Una Ciudadanía Críticaunclassified
“…Se trata de una tendencia que aparece en el contexto de una progresiva cristalización de valores globales, a la vez que la creciente problematización de sus implicancias ideológicas y políticas. Por ello, partiendo de la premisa de que la movilidad ha de entenderse también en términos de una nueva concepción axiológica (Muñoz, 2004;Tarrant, 2011), la presente investigación se inserta en tal discusión, indagando en los sentidos actuales de la movilidad estudiantil para luego preguntarse por los alcances de esta tendencia en el marco de transformaciones culturales de largo alcance. A partir de relatos de vida realizados con estudiantes daneses que cursaron durante el año 2011 un semestre en la Universidad de Valparaíso, en el marco de un programa de intercambio con la Universidad de Aalborg, exploramos el impacto de esta experiencia en las trayectorias de vida juveniles de procedencia nórdica y cultura socialdemócrata, para volver sobre la idea de ciudadanía global, las tensiones y los desafíos que ello supone.…”
Section: Introducción La Movilidad Estudiantil Y La Internacionalizaunclassified
See 1 more Smart Citation
“…Currently, the new trend of preparing local students to be global citizens focuses on international experiences. Generally, research findings tend to be highly positive about the "legion" benefits (Lenz & Wister, 2008, p. 84) Along with Senator Simon's Study Abroad Foundation Act, the Senate suggested that the federal government financially aid college students' studies abroad in order to ensure that American students [can] learn foreign languages and international knowledge for further improving global competencies of the U.S. (Tarrant, 2010). In addition, most higher education institutions are aware that the nation needs its future citizens to be equipped with sensitivity to global issues.…”
Section: Schattle (2009) Identified Five Ways Individuals Move Towardmentioning
confidence: 99%
“…However, articles on short-term exchange programs are scarce, though there are some publications. One article for example describes a short-term immersion program in the South Pacific (Tarrant, 2009). Another author describes a two-week student and faculty exchange program between a North American and a Korean university (DeLong, 2011) although that project took place in the design and fine arts departments of the two universities involved and not in the business administration departments as described here.…”
Section: Literature Reviewmentioning
confidence: 99%